The parent/child/teacher reading relation - Myrna Machet (Per Linguam : A Journal of Language Learning, 2008)
Becoming a reader involves gaining the meaning of the activities involved which includes the purposes, values and roles that are part of the activity. At home literacy is contextualised and a child becomes aware of the uses and practises of reading in his or her culture. This home based literacy is a more natural form of literacy and must be distinguishedfrom school based literacy which is a more organised, systematic literacy. Teachers need to be aware of the important role that preliteracy experience plays in a child's ability to learn to read successfully. They can then provide experiences that will help those children who come to school without the prerequisite emergent literacy skills to become good readers. Teachers will benefit from being aware of family literacy practices and encouraging parents to become involved in their children's reading, because this will help children to make reading and general literacy activities more meaningful. Children who become successful readers associate books with enjoyment and are therefore willing to make the effort to become readers. This is more likely to happen with the support from the family. Research indicates that a key predictor of student success is family involvement in children's education (Ginsburg, 1999:3). Om 'n leser te word, hou in dat betekenis gevorm moet word van die aktiwiteite wat by lees betrokke is, nl die doel, waardes en rolle wat deel van die aktiwiteite. Geletterdheid word by die huis gekontekstualiseer en 'n kind word bewus van die gebruike van en praktyke vir lees in sy of haar kultuur. Hierdie huisgebaseerde geletterdheid is die natuurlikste vorm van geletterdheid en moet onderskei word van skoolgebaseerde geletterdheid wat 'n meer georganiseerde sistematiese soort geletterdheid is. Onderwysers moet bewus wees van die belangrike rol wat voor-geletterdheidervaring speel in In kind se vermoe om suksesvol te leer lees. Hulle kan dan geleenthede organiseer wat daardie kinders sal help wat sonder die voorvereiste ontluikende geletterdheidsvaardighede skool toe kom om goeie lesers te word. Onderwysers sal voordeel daaruit trek as hulle bewus is van gesinsgeletterdheidspraktyke en ouers aanmoedig om betrokke te raak by hulle kinders se leesontwikkeling omdat dit kinders sal help om lees en algemene geletterdheidsaktiwiteite meer betekenisvol te maak. Kinders wat suksesvolle lesers word, assosieer boeke met genot en daarom is hulle gewillig am moeite te doen om lesers te word. Dit sal makliker gebeur met die ondersteuning van die gesin. Navorsing dui daarop dat 'n sleutelvoorspeller van 'n leerder se leessukses sy gesin se betrokkenheid by hulle opvoeding is (Ginsburg, 1999:3).